Curriculum for optical diagnosis of esophageal neoplasia and precursor lesions: European Society of Gastrointestinal Endoscopy (ESGE) Position Statement - Pouw, Roos E.; Weusten, Bas L. A. M.; Bergman, Jacques J.H.G.M.; Bisschops, Raf; Coron, Emmanuel; Dewint, Pieter; Elbe, Peter; Lorenzo-Zúñiga, Vicente; Hollenbach, Marcus; Barret, Maximilien; Dumoulin, Franz L.; Januszewicz, Wladyslaw; Manolakis, Anastasios C.; Maselli, Roberta; Parra-Blanco, Adolfo; Seewald, Stefan; Yakovenko, Vladyslav; Tham, Tony C. (Endoscopy, 2025)
Pre-adoptionEndoscopists performing upper gastrointestinal (UGI) endoscopy should train to recognize the appearance of early esophageal cancer and its precursor lesions, for Barrett neoplasia and for squamous neoplasia, to improve detection rates.Every endoscopist should have achieved competency in UGI endoscopy before commencing training in optical diagnosis in the UGI tract, and this requires personal experience of 300 UGI endoscopies and meeting the ESGE quality measures for UGI endoscopy.TrainingEndoscopists should undertake interactive training courses to improve diagnostic accuracy for esophageal preneoplastic and neoplastic lesions.Endoscopists should train with the Barrett’s Oesophagus-Related Neoplasia (BORN) module to improve detection and delineation for early Barrett’s esophagus-related neoplasia.Endoscopists should train in using the Prague classification to describe the circumferential and maximal extent of Barrett epithelium above the gastroesophageal junction.Endoscopists should train in using the Paris classification to describe suspected neoplastic lesions within both Barrett and squamous epithelium.Endoscopists should train in using virtual chromoendoscopy to assess both mucosal and vascular patterns in potentially neoplastic lesions in Barrett epithelium as being regular or irregular.When using acetic acid chromoendoscopy for Barrett’s esophagus inspection, endoscopists should be familiar with the appearance of neoplastic lesions by assessing loss of aceto-whitening and mucosal surface patterns.Endoscopists should train in using the Japanese Esophageal Society (JES) classification to describe esophageal squamous cell lesions, to estimate the likelihood of and degree of dysplasia, and in the case of squamous cell cancer, the invasion depth.